2022
DOI: 10.3389/fnins.2022.972882
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal developmental trends of functional connectivity in young children with infantile esotropia

Abstract: Previous studies have shown that functional networks are present at birth and change dynamically throughout infancy and early childhood. However, the status of functional connectivity is still poorly understood in patients with infantile esotropia (IE). The aim of this study is to investigate the developmental trends of functional connectivity in patients with IE during a critical period of growth and development. A total of 17 patients with IE (9 males and 8 females; mean age: 3.36 ± 2.03 years, age range: 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Interestingly, in this study, we demonstrated apparent negative correlations of the age at surgery with longitudinal FC changes in terms of CEN-DMN and V1N-LN, suggesting that the earlier the strabismus surgery is performed, the more benefits the IE patients will obtain in visual processing or emotion regulation, which emphasizes the impor-tance of the timely intervention for IE patients. More importantly, the findings provide robust evidence for our previous hypothesis from cross-sectional studies that corrective surgery for IE patients should be implemented in the early postnatal period to help the affected children to approach the normal developmental trajectories in FC (Guo, Chen, Liu et al, 2022a).…”
Section: Longitudinal Network-level Fc Changes In Iesupporting
confidence: 72%
See 4 more Smart Citations
“…Interestingly, in this study, we demonstrated apparent negative correlations of the age at surgery with longitudinal FC changes in terms of CEN-DMN and V1N-LN, suggesting that the earlier the strabismus surgery is performed, the more benefits the IE patients will obtain in visual processing or emotion regulation, which emphasizes the impor-tance of the timely intervention for IE patients. More importantly, the findings provide robust evidence for our previous hypothesis from cross-sectional studies that corrective surgery for IE patients should be implemented in the early postnatal period to help the affected children to approach the normal developmental trajectories in FC (Guo, Chen, Liu et al, 2022a).…”
Section: Longitudinal Network-level Fc Changes In Iesupporting
confidence: 72%
“…At baseline, 32 patients with IE and 30 control participants accomplished the resting‐state fMRI scanning and clinical evaluations. Partial data of cross‐sectional analysis have been reported (the original research includes 17 IE patients and 20 healthy controls) (Guo, Chen, Liu et al., 2022a ). The current study recruited additional participants for both IE group and control group and collected new postoperative longitudinal data of IE patients.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations